The RNA polymerase clamp interconverts dynamically among three states and is stabilized in a partly closed state by ppGpp - Duchi, D; Mazumder, A; Malinen, A; Ebright, R; Kapanidis, A (Oxford University Press, 2018)
RNA polymerase (RNAP) contains a mobile structural module, the ‘clamp,’ that forms one wall of the RNAP active-center cleft and that has been linked to crucial aspects of the transcription cycle, including promoter melting, transcription elongation complex stability, transcription pausing, and transcription termination. Using single-molecule FRET on surface-immobilized RNAP molecules, we show that the clamp in RNAP holoenzyme populates three distinct conformational states and interconvert between these states on the 0.1–1 s time-scale. Similar studies confirm that the RNAP clamp is closed in open complex (RPO) and in initial transcribing complexes (RPITC), including paused initial transcribing complexes, and show that, in these complexes, the clamp does not exhibit dynamic behaviour. We also show that, the stringent-response alarmone ppGpp, which reprograms transcription during amino acid starvation stress, selectively stabilizes the partly-closed-clamp state and prevents clamp opening; these results raise the possibility that ppGpp controls promoter opening by modulating clamp dynamics.